A causative analysis on ECDIS-related grounding accidents. (13th September 2020) - Turna, İdris; Öztürk, Orkun Burak
ABSTRACT: This study introduces an assessment concerning the use of Electronic Chart Display and Information System (ECDIS) in the safe navigation of vessels by considering the case studies whether the device played a role in grounding accidents. A total 80 investigation reports of grounding accidents from 2008 to 2018 were analysed. In 22 cases, one or more findings related to ECDIS and Electronic Navigational Charts (ENC) were identified. Twenty two accidents related to ECDIS or ENCs were re-analysed with 4M Overturned Pyramid (MOP) model to determine the characteristics and causes of accidents. Causative factors that related ECDIS in the cases have been listed and explained. Results indicate that ECDIS-related procedures and lack of training have led to incorrect settings of the device, especially alarm settings. The recommendations have been arranged that ECDIS devices, which offer much considerable information for the safe navigation of ships, are able to work more efficiently.